(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Iraqi industrial units face strong competition due to many problems including1- high production costs2- weak interest in studying the market3- lack of government support for their products4- dumping the market with imported products with specifications and a competitive price as well as adopting the traditional cost system in calculating costs that do not provide appropriate information for pricing decisions Which requires studying and analyzing these problems and dealing with them by adopting modern technologies so that they can compete, so the research aims to show the knowledge bases of technology Activity- Based Costing, with an indication of the role of technology Activity- Based Costing in rationalizing the tax In, and the research was based on a basic hypothesis that: (the technology Activity- Based Costing contributes to cost guidance), and that the most prominent finding of the research is the adoption of (ABC) technology in the distribution of indirect costs of the laboratory on the basis of laboratory activities and is represented in seven activities (1-transport Raw materials from stores, 2-separation3-sewing4-traction5-quality inspection 6-packaging7-transfer of complete production to stores) It led to a fairer distribution of the indirect costs by identifying the costs of activities that add value and the costs of activities that do not add value and thus helping the administration to identify the costs of activities that do not add value and amounting to (136453031) dinars and thus contributed to the rationalization of costs as these costs do not have Link to the factory, taking into account the required level of quality and maximizing the level of customer benefit..